Literasi Digital Orang Tua: Melindungi Anak dari Risiko Online - Sembiring, Sintaria (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
The rapid advancement of digital technology has transformed how children access and use the internet, offering opportunities for learning and socialization while exposing them to risks such as cyberbullying and harmful content. This study examines parental digital literacy across six dimensions: knowledge of technology, security settings, usage policies, monitoring activities, communication, and risk awareness. Data were collected from 179 mothers with children under 15 through structured questionnaires. Findings reveal generational and educational disparities in digital literacy. Generation Y demonstrated strong technological knowledge and security practices but lacked awareness of digital risks. Generation Z excelled in monitoring activities but faced challenges in communication and usage policies, while Generation X showed strength in communication and risk awareness but required improvement in security settings and practical technology use. Educationally, mothers with advanced degrees had greater knowledge and risk awareness but struggled with application skills, while those with lower education levels exhibited lower proficiency overall. This study highlights the need for tailored interventions, including cross-generational training and targeted educational programs, to address gaps in parental digital literacy. These efforts aim to foster safer digital environments for children. Future research should explore socioeconomic factors and evaluate the long-term impact of interventions to enhance digital parenting.